Judicial Reforms ‘Under Pressure’: The New Map/Organisation of the Portuguese Judicial System - Dias, João Paulo (2018)
The implementation of the new map/organisation of the judicial system in Portugal, approved in 2013, has become an example of an externally induced reform. The biggest reform process ever seen within the justice system took place under the rule of the Troika in Portugal, together with budget cuts to the justice system as a result of the Portuguese financial crisis (since external financial support required strict austerity measures). The key word was therefore concentration: the concentration of courts, litigation and resources. The reform of the organisation/map of the judicial system reduced 232 lower courts to 23 district courts, each with jurisdiction over a larger territory and greater specialisation. Most of the former smaller courts were transformed into local sections or branches of the now streamlined judicial system, in an attempt to retain some proximity to citizens. However, a significant number of cases are now heard in district courts rather than in these local courts. This reorganisation, including a totally new management model, led to profound organisational changes and altered the relationship between citizens and the justice administration. The aim of this article is to discuss the context, actors and politics involved in this judicial reform process as an example of a top-down strategy, designed under pressure in response to an external ‘order’ and influenced by internal actors, which failed to consider citizenship and democracy.